Estilos de aprendizaje y logros de aprendizaje en el área de comunicación en estudiantes del sexto grado de primaria de la Institución Educativa Nº 60080, Ramón Castilla 2023 - Garcia Rodriguez, Wendy Patricia (2024)
Objective: Determine the relationship that exists between learning styles and learning achievement in the area of communication of students in the sixth grade of primary school at the I.E. No. 60080 of the Ramón Castilla district, during the 2023 school year. Materials and methods: The research design was non-experimental, field, correlational and transectional. The population and sample was 110 students. The data collection instruments were two question questionnaires. It was observed that: the results obtained from the statistical analysis using the Spearman coefficient demonstrated a significant relationship between learning styles (active, reflective, theoretical and pragmatic) and learning achievements, with correlation coefficients that vary between r= 0.502 and r=0.632, and a significance less than 0.01. Conclusion: The correlation is positive but moderate.